INTERSEKSI TINDAK TUTUR DALAM KOMIK TINTIN - ATHIAH, RATNA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This minithesis has the title Speech Act In The Series Comic Tintin. This research is aimed at describing the linguistic form of speech act used in the conversation of the series Comic Tintin. This research is conducted based on four steps. The first step is selecting the population and determining the sampleof the research. The second step is providing the data. The third step is analyzing the data. The fourth is presenting of the results analysis. Having been analyzed, it was found that there are various forms of speech act used in the Comic Tintin. Even from the Comic Tintin we can find the intersection of speech act, they are direct speech act-literal, indirect speech act-non literal, direct speech act-non literal, and indirect speech act-non literal. Based on the types of speech act used in the Series of Comic Tintin influencing the selection of the forms speech act are the age of participants, the character of participants, the emotion of participants when the speech act done, and the level of the familiarity among the participants. All factors mentioned above influence the choise of the forms of the speech act.